Application of geothermal energy and its environmental problems in Turkey. (2015) - Baba, Alper
Human beings have been benefiting from geothermal energy for different uses since the dawn of the civilisation in many parts of the world. One of the earliest uses of geothermal energy was for heating and it was used extensively by Romans in Turkey. The Aegean region is favoured by a large number of thermal springs known since ancient times. However, it was first in the 20th century that geothermal energy was used on a large scale for direct use and electricity generation. The country's installed heat capacity is 2, 705 MWt for direct use and 322.39 MWe for power production. In parallel to developing geothermal energy applications in Turkey, many sites are now experiencing problems such as water contamination associated with geothermal fluid. Especially, the high temperature solution of elements and compounds, causes operational limitations in geothermal power plants. These limitations are due to the severe scaling and corrosion of geothermal fluid.